Pengaruh Penerapan Prinsip Good Governance Terhadap Peningkatan Kualitas Pelayanan Publik Pada Pemerintahan Kenagarian Kumango Kecamatan Sungai Tarab Tahun 2021 - Rolan Syafril; Dewi Dahlan (Politik Islam, 2022)
Problem in this reseach is good governance and public services in the Kumango government Sungai Tarab District in 2021. This study aims to determine the effect of implementing good governance on improving the quality of public services in the Kumango government, Sungai Tarab district The type of research used in quqntitative research with correlation tecniques to find the effect between variables X and Y. The population in this syudy is 1192 people with a sampe 92 people. The sampling technique was using simple random sampling. The collection technique used is a likert scale using research instruments on a good governance scale and public service. The processing is done statistically non parametric with the help of SPSS version 20.00 for windows The results show that there is an influence in the application of good governance principles on the quality of publik services in the Kumango government Sungai Tarab District in 2021. This can be seen from the analyst using the sperman rank test with the help of SPSS for windows, the results obtained ar rs=0,649 with a significance value (p<0,01) is smaller than (p<0,05). Based on the result of the hypothesis shows that Ha is accepted and Ho is rejected